Making environmental policy work with civic science: the intermediary role of expert citizens at the Japanese local level - Takao, Yasuo (Routledge, 2015)
The aim of the present article is to examine the importance of public participation in the production and use of environmental science, with special reference to “expert citizens” who can facilitate and mediate between expert knowledge and lay people. The study of expert citizens is largely unexplored in Japan's environmental policy. As uncertainty, inherent in the complexity of environmental science, increases, there are calls for refashioning expert knowledge into a more citizen–expert interactive governance. In the USA, the way that lay people can participate in scientific knowledge application and policy-making is organised through grassroots and national environmental organisations, such as the National Resources Defense Council. In Japan, such professional associations that build networks of interaction with scientific experts, policy-makers, interest groups and the media, have yet to emerge on a wider scale. Nonetheless, voluntary citizens individually or collectively have developed their expertise over many years and have begun to play an intermediary role at the local level. This article will analyse the potential roles of expert citizens by conducting the case studies of two Japanese localities, Shiki and Joyo cities.